Indigenous aquatic and minor vegetables - Dubey, Rakesh Kumar; Singh, Vikas; Devi, Jyoti; Singh, P M; Singh, Jagdish (Indian Horticulture, 2020)
Indigenous vegetables have made an important contribution to food and nutritional security and also enhanced the livelihoods of marginal and smallholder farmers. Indigenous vegetables have been shown to be rich in micronutrients such as iron, zinc, pro-vitamin A and phytochemicals that help protect people against non-communicable diseases. Indigenous aquatic vegetables are predominantly in vogue where they are naturally available in plenty. Areas rich in water bodies like lakes, lagoons, ponds, ditches, marshy wet places are natural abode of most of the aquatic vegetables. Communities dominated in the wetland areas of the India do not only get their requirements of vegetables completed, it has been indispensable part of their life.